Comparison of the frequency of bacterial and viral infections among children with community-acquired pneumonia hospitalized across distinct severity categories: a prospective cross-sectional study - Nascimento-Carvalho AC; Ruuskanen O; Nascimento-Carvalho CM (BIOMED CENTRAL LTD, 2022)
Background: The comparison of the frequencies of bacterial and viral infections among children with community-acquired pneumonia (CAP) admitted in distinct severity categories, in an original study, is lacking in literature to-date. We aimed to achieve this goal.Methods: Children aged 2-59-months-old hospitalized with CAP were included in this prospective study in Salvador, Brazil. Clinical data and biological samples were collected to investigate 11 viruses and 8 bacteria. Severity was assessed by using the World Health Organization criteria.Results: One hundred eighty-one patients were classified as "non-severe" (n = 53; 29.3 %), "severe" (n = 111; 61.3 %), or "very severe" (n = 17; 9.4 %) CAP. Overall, aetiology was detected among 156 (86.2 %) cases; viral (n = 84; 46.4 %), bacterial (n = 26; 14.4 %) and viral-bacterial (n = 46; 25.4 %) infections were identified. Viral infection frequency was similar in severe/very severe and non-severe cases (46.1 % vs. 47.2 %; p = 0.9). Pneumococcal infection increased across "non-severe" (13.2 %), "severe" (23.4 %), and "very severe" (35.3 %) cases (qui-squared test for trend p = 0.04). Among patients with detected aetiology, after excluding cases with co-infection, the frequency of sole bacterial infection was different (p = 0.04) among the categories; non-severe (12.5 %), severe (29.3 %) or very severe (55.6 %). Among these patients, sole bacterial infection was independently associated with severity (OR = 4.4 [95 % CI:1.1-17. 6]; p = 0.04) in a model controlled for age (OR = 0.7 [95 % CI:0.5-1.1]; p = 0.1).Conclusions: A substantial proportion of cases in distinct severity subgroups had respiratory viral infections, which did not differ between severity categories. Bacterial infection, particularly pneumococcal infection, was more likely among severe/very severe cases.